Gift Box / Nur Syamimie Hazuki - Hazuki, Nur Syamimie (2021)
Business opportunity are about how we related the case study and business and apply it on our business plan to be a successful entrepreneur and how we identify any course of production of beginning until the end. It also teaches us the strategic plan to recognize any problems with this business. I choose the business of selling gift boxes to give to someone like a best friend, boyfriend, crush, or someone special for this assignment of business opportunity. I am a dropship of the team Jwelsyrv. The gift box was suitable to give to all ages. The reason why I love selling this type of gift box because I loved to made people felt excited, surprised, and happy. The gift box means that I put the things like chocolate, polaroid, handbag, cap, ring, and others in one box and ready to deliver to the customer. The customer will get surprised when the box was delivered. The main purpose of selling gift boxes is to make people who want to make it easier for someone to give a gift to a friend without the need to go to the store to buy their own. The customer only chooses the gift box that attracted them. The price is affordable to buy. Customers also can custom their other either they want to change or add on a thing in the box. But surely, the customer needs to pay more than the original price.